Outside CEOs and innovation - Cummings, Trey; Knott, Anne Marie (Strategic Management Journal, 2018)
Research Summary: Innovation is the principle driver of firm and economic growth. Thus, one disturbing trend that may explain stagnant growth is a 65% decline in firms’ R&D productivity. We propose that the rise of outside Chief Executive Officers (CEOs) may be partially responsible for the decline because those CEOs are more likely to lack technological domain expertise necessary to manage R&D effectively. While this proposition was motivated by interviews with Chief Technology Officers (CTOs), we test it at large scale. We find that firm R&D productivity decays during the tenure of outside CEOs relative to that of inside CEOs. We further find this effect is more pronounced for firms with high R&D intensity and for firms employing outside CEOs with more remote experience, lending circumstantial support for the underlying assumption regarding lack of expertise. Note that this is not a call for boards to avoid outside CEOs, rather it is recommendation to consider the implications for innovation. Managerial Summary: While outside CEOs offer advantages over internal candidates, we argue one unintended consequence is weaker innovation. This argument was prompted by two coincident trends: a 65% decline in companies’ R&D productivity and a doubling of outside Chief Executive Officers (CEOs). The argument was reinforced by interviews with Chief Technology Officers (CTOs), who recounted shifts in orientation from R&D as an investment to R&D as an expense that occurred shortly in response to a new CEO. We felt this shift was more likely with outside CEOs because they may lack technological domain expertise necessary to effectively manage R&D. Our results are consistent with the argument—company R&D productivity decreases under outside CEOs. Note, however, that we don’t advocate avoiding outside CEOs, rather we recommend R&D firms consider technological domain expertise during CEO hiring.